Load spectrum construction of a jack-up offshore platform lifting system - MAI Zhihui; ZHOU Zhanpeng; TIAN Chengquan; WAN Zhenping (Jixie chuandong)
ObjectiveTaking the rack-pinion lifting system of a jack-up offshore platform as an example, the random load data of the platform lifting system was collected for 6 months, and the construction technology and method of load spectrum for jack-up offshore platform lifting systems was studied.MethodsAccording to the load characteristics of the lifting system, the rain flow counting method was adopted to process the measured main shaft loads, and the rotation counting method was used to convert them into gear load spectra. The programmed load spectrum of the offshore platform lifting system was developed, and a method for load spectrum collection and compilation of offshore platform lifting systems was proposed. The fatigue life of the climbing gear in the lifting system was analyzed based on the load spectrum.ResultsThe position with the maximum damage degree was the contact area of the climbing gear’s positive tooth surface, with a damage degree of only 1.55×10⁻³ and a fatigue life of approximately 1.29×10⁶ h, which far exceeds the design life.